Sharia-Based Corporate Social Responsibility Disclosures for Responsible Innovation: What are the Benefits to Overcome the Grand Challenge? - Sasongko, Ananta Wahyu; Nugraha, Farhani Kautsar (Business Management Research, 2023)
The grand challenges of poverty, inequality, hunger, war, climate change, and deforestation impede the advancement of sustainable development. These difficulties can only be addressed by fundamental changes in behavior, production modes and processes, and business practices in general. In this paper, we will create the notion of corporate social responsibility disclosures (CSRD) based on shari’ah and analyze the potentials and limitations for the advancement of sustainable development and overcome the grand challenge. This study approach incorporates theoretical and empirical insights into the ways in which alternative forms of CSRD might assist in addressing grand challenges. Thus, the study provides examples of CSRD and corporate governance that might assist in producing ideas that do good and avoid harm in order to solve this worldwide issue. However, this study is limited by the researcher’s subjectivity, which has a significant impact on the outcome of proposing a new form of CSRD to address humanity’s grand challenges.